Long sleep duration and cardiovascular disease: Associations with arterial stiffness and blood pressure variability - Hideaki Matsubayashi; Michiaki Nagai; Keigo Dote; Yuda Turana; Saulat Siddique; Yook‐Chin Chia; Chen‐Huan Chen; Hao‐Min Cheng; Huynh Van Minh; Narsingh Verma; Jam Chin Tay; Boon Wee Teo; et al. (The Journal of Clinical Hypertension, 2021)
Abstract Although short and long sleep duration are both risk factors of cardiovascular disease (CVD), the recent meta‐analyses have been shown that long sleep duration was closely associated with CVD mortality. While the specific mechanism underlying the association between long sleep duration and CVD remains unclear, long sleep duration was shown to be associated with arterial stiffness and blood pressure variability (BPV) in many Asian populations. This review article will focus on the pathophysiology of long sleep duration, arterial stiffness, BPV and their effects on CVD. To set the stage for this review, we first summarize the current insights for the relationship between long sleep duration and CVD in relation to arterial stiffness and BPV.